Prospects of the Presidential and the Semi-Presidential Systems in the Context of Nepal - Pulami Magar, Rudra Bahadur (A Bi-annual South Asian Journal of Research & Innovation, 2025)
Nepal’s current parliamentary system has suffered repeated executive-legislative crises, unstable coalitions, and eroding public trust. This paper reviews whether adopting a presidential or semi-presidential model could improve stability and governance. Drawing on comparative theory and international experience, it examines how these systems organise executive power and how they might suit Nepal’s federal, multiethnic context. Presidential systems feature an independently elected executive separate from the legislature. In contrast, semi-presidential regimes blend a popular president with a prime minister who is accountable to parliament. Executive powers are divided in various ways, often benefiting the president under certain designs. The analysis finds that a presidential model can offer clear leadership and fixed-term stability but risks authoritarian drift unless strong checks exist. A semi-presidential model can combine stability with legislative accountability if its constitutional design is clear, but unclear dual roles can generate conflict. In Nepal’s context, careful institutional safeguards would be needed. The study concludes that systemic change alone cannot cure fundamental political culture issues; long-term success would depend on broad reforms to parties, institutions, and civic culture. Findings are intended to inform Nepali policymakers by synthesising theory and global lessons for deliberating possible governance reforms.